Decentralized, On Demand Server System Using Smartphones - Sah, Anish; Dahal, Manita; Sharma, Pratik; Bhattarai, Sukirti; Satyal, Sanjivan (KEC Journal of Science and Engineering, 2023)
The advancement in technology has impelled entities to use websites for communication. Some websites such as result publication sites usually have low traffic flow except on days like result publication. The sudden spike in traffic flow makes the websites respond slow or even crash thus requiring a dynamic allocation of servers. This project, “Decentralized, On Demand Server System Using Smartphones”, is designed and implemented to use smartphones as on-demand servers for hosting websites. The system consists of three components: ‘System Website’ controls the overall system and ‘Smartphones’ act as servers for the ‘Client Websites’ that are to be hosted. Smartphones can be registered and become servers/hosts using a mobile application. A client website is first uploaded to the system and distributed to the registered smartphones. When an end-user requests a website, the request is redirected by the System Website to the smartphone which holds the requested site. A connection is established where the smartphone hosts the website to the end-user. After the hosting is completed, the host becomes free. In case of network failure, a network is established using different host that makes the system reliable.